2017
DOI: 10.18632/oncotarget.21862
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgetin induces autophagic cell death through p62/SQSTM1-mediated autolysosome formation and redox setting in non-small cell lung cancer

Abstract: Promoting cell death by autophagy could be a novel treatment for cancer. The major player in autophagy, p62, serves as a good therapeutic target. Ginkgetin, a biflavonoid from Ginkgo biloba leaves, exhibited promising anticancer activity in non-small cell lung cancer cell lines, with an IC50 lower than that of cisplatin. This anticancer effect of ginkgetin was illustrated in a xenograft nude mouse model. Ginkgetin induced autophagic cell death in A549 cells, and this effect was markedly reversed by chemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…Different studies on ginkgetin have proposed a series of pharmacological activities [28]. Ginkgetin exerts inhibitory effects on different types of cancers including prostate cancer [29], breast cancer [30], non-small cell lung cancer [31], and colon cancer [32]. Moreover, ginkgetin has been shown to exhibit cytotoxic effects in ovarian and prostate cancers [29,33].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies on ginkgetin have proposed a series of pharmacological activities [28]. Ginkgetin exerts inhibitory effects on different types of cancers including prostate cancer [29], breast cancer [30], non-small cell lung cancer [31], and colon cancer [32]. Moreover, ginkgetin has been shown to exhibit cytotoxic effects in ovarian and prostate cancers [29,33].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on various substances have reported that autophagy plays a paradoxical role in anti-tumor therapy. Induction of autophagic cell death by small molecules contributes to the enhancement of anti-tumor activity of chemotherapy or radiation therapy, whereas autophagy-dependent anti-apoptotic responses induced by chemotherapy have negative impacts on anti-tumor treatment through inhibition of the mTOR pathway 17,18 . To our best knowledge, no association between anti-tumor effects of PAM and autophagy has been reported.…”
mentioning
confidence: 99%
“…Ginkgetin, a bi avonoid from Ginkgo biloba leaves, exhibited cytotoxicity in cultured A549 cells 15 . Here, ginkgetin was combined with DDP at various concentrations in applying onto cultured A549 cells.…”
Section: Ginkgetin Promotes Ddp-induced Cytotoxicitymentioning
confidence: 99%
“…The concentration of total glutathione, or GSSG, was calculated via standard curve, and GSH level was calculated as: GSH = (total glutathione-GSSG) × 2. The ratio of GSH/GSSG was calculated as [GSH]/[GSSG].Xenograft nude mice modelThe establishment of xenograft nude mouse model and ginkgetin preparation were conducted as previously described15 . Brie y, when tumours on transplanted nude mice reached around 100 mm 3 , the mice were randomized divided into eight groups: control, ginkgetin, DDP, ginkgetin + DDP, UAMC 3203, ginkgetin + UAMC 3203, DDP + UAMC 3203, ginkgetin + DDP + UAMC 3203.…”
mentioning
confidence: 99%